Stories on stage - Shepard, Aaron (Friday Harbor, Washington : Shepard Publications, 2017)
"Stories on Stage" is a collection of reader's theater scripts for young readers, adapted from stories by fifteen different authors, including Louis Sachar, Nancy Farmer, Russell Hoban, Wanda Gag, and Roald Dahl. Coming from such genres as humor, fantasy, and multicultural folktales, stories were selected for their dramatic quality, literary value, and appeal to young people. While focusing on ages 8 to 15, the collection features a wide range of reading levels.
Millions of cats / Wanda Gag -- Harriet / Florence Parry Heide -- The legend of Lightning Larry / Aaron Shepard -- Mr. Bim's bamboo / Carol Farley -- Three sideways stories from Wayside School / Louis Sachar -- The jade stone / Caryn Yacowitz -- Talk / Harold Courlander -- The bean boy / Monica Shannon -- How Tom beat Captain Najork / Russell Hoban -- Tapiwa's uncle / Nancy Farmer -- The kid from the commercial / Stephen Manes -- The fools of Chelm / Steve Sanfield -- Mr. Twit's revenge / Roald Dahl -- Mouse Woman and the snails / Christie Harris -- Westwoods / Eleanor Farjeon
Keywords: READER'S THEATER